Rock slope stability analysis based on terrestrial LiDAR on Karst Hills in Kinta Valley Geopark, Perak, Peninsular Malaysia - Muhammad Afiq Ariff Hellmy,; Ros Fatihah Muhammad,; Mustaffa Kamal Shuib,; Ng, Tham Fatt; Wan Hasiah Abdullah,; Aishah Abu Bakar,; Kugler, Ralph (Penerbit Universiti Kebangsaan Malaysia, 2019)
The use of modern mapping technology is necessary in assessing slopes and cliffs, especially in tropical countries as it is mostly inaccessible and covered with thick vegetation which restricts the conventional data collection to only at the base of the cliff. Overhanging and sub-vertical characteristics of tropical karst hills in Kinta Valley together with highly fractured and day-lighting joints increase the possibility of rock slope failure. The problem statement of this research is how Terrestrial Laser Scanning (TLS) can assist the traditional survey in slope characterization. The main objective of this research was to assess the stability of the limestone hills in Kinta Valley based on the output provided by terrestrial LiDAR and scanline survey method. TLS helps engineers and geologists to collect a high number of discontinuity data where it is inaccessible for manual compass data measurement. A total number of about 13 cliffs on 4 limestone hills were assessed. Gunung Lang and Kek Lok Tong show major potential failure trending towards east, Gunung Lanno towards southwest, Kwan Yin Tong towards west, and Gunung Cheroh with three directions of failure which are pointed towards the south, southwest and southeast direction. The overall results showed that the orientation of the major joint sets and the direction of the failure greatly influence the karst hills morphology in the Kinta Valley. The integration of LiDAR method with the manual compass clinometer has become a better approach to assess the stability of limestone hills and other rock slope in the possible future.